HUBUNGAN KECUKUPAN VITAMIN C DAN ZAT BESI DENGAN KEBUGARAN JASMANI ATLET PENCAK IPSI LAMONGAN - Kartika Indaswari Dewi; R. Bambang Wirjatmadi (Universitas Airlangga, 2017)
Pencak silat is a sport that requires agility, speed, balance and body slenderness. Vitamin C and iron are part of the micronutrients that can support the athlete’s physical fitness. The aims of this study was to determine the relationship between the adequacy of vitamin C and iron with physical fitness of pencak silat athletes IPSI Lamongan. This study used observational analytics with case-control design with 20 samples of athletes, divided into 10 cases and 10 controls. The result of analysis from 2×24 hour food recall method in each case group was 9 (90%) athletes did not meet the requirement of vitamin C (<77%) and 8 (80%) athletes did not meet the requirement of iron and control group there were 7 (70 %) Athletes are not sufficient for vitamin C (<77%) and 6 (60%) of athletes are inadequate for iron (<77%). From the statistical test using chi-square, it was found that there was no significant relationship between vitamin C and iron adequacy with physical fitness (TKJI) with p=0.580 and p=0.620. Conclusion: adequacy level of vitamin C and iron of pencak silat athletes IPSI Lamongan is not meet their requirement yet.